Livrarias, memória e identidade: a importação de livros no Brasil e a trajetória da livraria Leonardo da Vinci no Rio de Janeiro - Baptistini, Flávia Maria Zanon (2017)
This research aims to rescue Leonardo da Vinci Bookshop’s history based in Rio de Janeiro, which had been in the care of the same family for more than sixty years and was sold at the beginning of 2016. It was acknowledged nationally for its high-quality imported books catalog from all over the world and for the high-standard bookseller’s performance of the founder and her staff, the Da Vinci Bookshop – as well as other previous bookshops that proved to be part of the city’s memory. Its relationship with the urban everyday life enabled not only the production and the development of the humanistic knowledge in the old Republic capital, but also promoted ways of sociability of several scholars living in Rio de Janeiro during the second half of the 20th century. The purpose of this study is to reflect about the symbolic dimension of certain kinds of commercial activities, focusing on the bookseller diversity in the cultural life of the cities. Besides being a purchase point, nowadays the few remaining bookshops are used as leisure centers and a place designed mainly for literary activities and they make part of the powerful international companies